Modifikasi Skor TIMI sebagai Model Prediksi Mortalitas 30 Hari Pasien STEMI Muda - Mansur, M. Tasrif; Yamin, Muhammad; Rusdi, Lusiani; Abdullah, Murdani; Karim, Birry; Rumende, Cleopas Martin; Marbun, Maruhum Bonar H.; Shatri, Hamzah (Jurnal Penyakit Dalam Indonesia, 2023)
Introduction. Cardiovascular disease is a leading cause of death worldwide. Three-quarters of these deaths occur in lowand middle-income countries among individuals in their productive years. ST-segment elevation myocardial infarction (STEMI) is a dangerous manifestation of coronary artery disease (CAD) and can lead to sudden death. Smoking and a family history of early CAD are major risk factors for STEMI cases. However, their role in any risk stratification system for patients has not been clearly established. The most widely used score in assessing the prognosis of STEMI patients is the TIMI score, but its accuracy in the young patient population is still unknown. The objectives of this study were to determine the proportion of mortality in young STEMI patients at RSCM, validate the TIMI score in young patients, and develop a risk stratification system for young STEMI patients. Methods. This research is a retrospective cohort study using medical record data from the Dr. Cipto Mangunkusumo National General Hospital (RSCM) on patients aged ≤50 years who were treated for ST-elevation myocardial infarction (STEMI) from 2018 to 2022. Univariate analysis was conducted to obtain subject characteristics and the 30-day mortality proportion of young STEMI patients. Bivariate Cox regression analysis was performed to examine the relationship between smoking and a family history of early coronary artery disease (CAD) with 30-day mortality. The TIMI score was validated in the study subjects of young patients. Multivariate analysis was conducted to obtain a new prediction model, and the model’s discriminatory performance was assessed using the area under the ROC curve (AUC), and model calibration was modified using the Hosmer-Lemeshow test. Results. A total of 164 study subjects were included. There were 107 patients (65.2%) with a smoking risk factor, while 39 patients (23.9%) had a family history of early CAD. The proportion of 30-day mortality among young patients was 7.9% (13 individuals). Statistical analysis showed that there was no correlation between 30-day mortality in young STEMI patients and a history of smoking (HR 0.0441 (95% CI 0.148-1.312)) or a family history of early CAD (HR 0.567 (95% CI 0.126- 2.559)). The TIMI score showed good predictive ability for 30-day mortality in young STEMI patients, with an AUC value of 0.836 (95% CI 0.717- 0.956). The combination of the TIMI score with the smoking history variable demonstrated good discriminatory performance in predicting 30-day mortality among young STEMI patients, with an AUC value of 0.875. However, when comparing the AUC values between the TIMI score and the TIMI score with the addition of the smoking history factor, no significant increase in accuracy was observed (p-value=0.215). Conclusions. The TIMI score demonstrates good discrimination and calibration in predicting 30-day mortality among young STEMI patients. The TIMI score, when combined with the smoking history factor, shows improved discriminatory performance and calibration in predicting 30-day mortality among young STEMI patients compared to the pure TIMI score but does not significantly enhance the accuracy.